2022
DOI: 10.31757/euer.516
|View full text |Cite
|
Sign up to set email alerts
|

Aspirations Are Not Enough: Barriers to Educational Attainment for Youth Involved with Child Welfare

Abstract: Children of families involved with child welfare services are considered high-risk and are vulnerable to developing problems in a number of domains. In particular, educational achievement among this population tends to be lower relative to general population peers. The goal of this qualitative study was to understand the educational aspirations and subsequent pathways of young adults with former child welfare involvement. Semi-structured interviews were conducted with seven young adults (mean age of 31 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…As Dimakosa et al (2022) pointed out, even for those young people in care who have developed aspirations, knowing how to move from aspiration to realization remains another challenge. The results of their study, which involved seven young adults in Ontario who had been involved with child welfare, showed that although the youth had high hopes for their futures, they still faced many obstacles.…”
Section: Supporting the Development Of Aspirationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Dimakosa et al (2022) pointed out, even for those young people in care who have developed aspirations, knowing how to move from aspiration to realization remains another challenge. The results of their study, which involved seven young adults in Ontario who had been involved with child welfare, showed that although the youth had high hopes for their futures, they still faced many obstacles.…”
Section: Supporting the Development Of Aspirationsmentioning
confidence: 99%
“…Even though their path to achievement is likely to be more arduous than that of their peers (Dimakosa et al, 2022), different avenues are available to help young people from placement realize their aspirations (Tzenis, 2018). Tzenis (2021) suggested that programs in which youth document their plans for their futures should incorporate activities that help them learn to rely on social support and to recognize possible obstacles, such as social barriers.…”
Section: Supporting the Development Of Aspirationsmentioning
confidence: 99%